Optical image subtraction through speckle modulated by young fringes - Rabal, Héctor J. (1980)
A new method for subtracting images is proposed. It is based on assigning complementary Young's fringes to the speckles of the common parts of two images. In this way, carrier frequency is cancelled, and “a-posteriori” spatial filtering shows only noncommon parts. Suggestions on applications of the method are briefly commented.